Parking and the city. - (:unkn) unknown (Routledge, 2018)
The book shows that city parking policies subsidize cars, encourage sprawl, degrade urban design, prohibit walkability, damage the economy, raise housing costs, and penalize people who cannot afford or choose not to own a car. Using careful analysis and creative thinking, the author recommended three parking reforms: (1) remove off-street parking requirements, (2) charge the right prices for on-street parking, and (3) spend the meter revenue to improve public services on the metered streets.Parking and the City reports on the progress that cities have made in adopting these three reforms. The successful outcomes provide convincing evidence that the proposals are not theoretical and idealistic but instead are practical and realistic. The 51 chapters by 46 authors in Parking and the City show how reforming our misguided and wrongheaded parking policies can do a world of good.
Keywords: Verkehr; Stadtverkehr; Verkehrsplanung; Stadtplanung; Flächennutzung; Ruhender Verkehr; Parken; Parkplatz; Stadtplanung; Parkraumbewirtschaftung; Beispielsammlung